THE EFFECTIVENESS OF PAIR CHECK METHOD IN WRITING ANNOUNCEMENT TEXT AT CLASS X SMA SWASTA RAUDHATUL HASANAH ACADEMIC YEAR 2021/2022 - Fauziah Ajmi; Sabrun Jamil; ABDUL HALIM (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study deals with the effectiveness of pair check method in writing announcement text at class X SMA Swasta Raudhatul Hasanah Academic Year 2021/2022. Its objective is to find out whether the use pair check method has a significance effect in announcement text writing. Population and samples used in this study were all students of class X total 27 students. The method used in this study is an experimental method with a one group as pretest and posttest design .This study was carried on using quantitave method. The data was analysed by using t-test.The researcher found the pretest mean = 51,67 deviation standard = 3,67 and experienced an increase in the posttest mean = 81,85 deviation standard = 2,46. From this analysis, writer found that guided pair check method has significane in teaching writing announcement text. It can be proved by the result of the analysis showed that “ ” observed about 35,50 was higher than “ttable” about 2,056 with the level significance is 0,05% it implies that the teacher of English should use pair check method in teaching announcement text writing so that the teaching and learning process can be successful.